ANALISIS FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI ISLAM DI SUMATERA BARAT - Effendy, Yolanda; Andriawan, Andriawan; Rawati, Mesis; Hawari, Rayzul; Al-Amin, Al-Amin (STAI Darul Qalam Tangerang, 2024)
This study aims to look at the factors influencing the growth of the Islamic economy in West Sumatra. This type of research is library research, namely by looking for research data or information through reading scientific journals, reference books, published economic growth reports and other publication materials that support this writing. The data used are secondary data collected from various relevant literature. Various data findings and information collected, as well as carried out analysis and synthesis to explore research questions. The results showed that economic growth is influenced by certain factors such as human funding, existing human and natural resources, the role of existing Islamic financial institutions and available technological advances